L2 Learners’ Perceptions of the Benefits of Authentic Material Use in Preparation for Academic IELTS Reading Comprehension Tests - Tran Quoc Thao,; Hoang Thi Quynh Nhu, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
Teaching materials hold a vital position in English language learning and teaching, and have gained a great deal of attention from many EFL teachers and material designers. It has been recognised that authentic materials (AMs) can be used as a potential source of material for language learning and teaching. However, there has been ongoing controversy when it comes to choosing them for reading comprehension. This study aims at investigating L2 learners’ perceptions of the benefits of AM use for reading comprehension in IELTS preparation courses at a Ho Chi Minh City-based language centre in Vietnam. Data were collected from 150 learners who completed a questionnaire. Ten of them participated in semi-structured interviews. The results indicated that L2 learners believed that the use of AMs was beneficial as it could enhance their English language, cultural awareness, learning motivation, and reading strategies. The finding-based implications are presented to teachers, learners, and material designers in an attempt to enhance the quality of English language teaching in general and the use of AMs specifically.Received 20th December 2023; Revised 25th February 2024; Accepted 15th March 2024